ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL BERPIKIR KRITIS PADA SISWA KELAS VIII DI SMP N 1 AMPEK ANGKEK - Lisa Fatmawati; Risnawita; Ulva Rahmi; Haida Fitrii (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the types of errors made by eighth-grade students in solving mathematical critical thinking problems on the topic of a Two-Variable Linear Equation System (SPLDV) at SMP Negeri 1 Ampek Angkek. The background of this study is the low level of students' critical thinking ability, which has never been analyzed systematically at the school, so teachers find it difficult to design an appropriate learning strategy. This research used a qualitative descriptive approach involving 30 eighth-grade students selected through purposive sampling. Data were collected through a written test consisting of four essay items based on Facione's critical thinking indicators and through observation, then analyzed descriptively using the Newman Error Analysis procedure, which classifies errors into comprehension, transformation, process skill, and encoding categories. The results show that students made errors in all four categories at varying levels: comprehension error 80.83%, transformation error 51.66%, process skill error 76.67%, and encoding error 83.33%. The most dominant error was encoding, followed by comprehension, process skill, and transformation. These findings indicate that most students have not been accustomed to writing a complete final conclusion and still have difficulty identifying the information given in a problem, especially under limited working time. The results are expected to provide teachers and schools with a clear picture of students' difficulties at each stage of problem solving so that appropriate learning strategies can be designed to improve students' mathematical critical thinking skills.